2011
DOI: 10.1007/jhep09(2011)082
|View full text |Cite
|
Sign up to set email alerts
|

The earth matter effects in neutrino oscillation experiments from Tokai to Kamioka and Korea

Abstract: We study the earth matter effects in the Tokai-to-Kamioka-and-Korea experiment (T2KK), which is a proposed extension of the T2K (Tokai-to-Kamioka) neutrino oscillation experiment between J-PARC at Tokai and Super-Kamiokande (SK) in Kamioka, where an additional detector is placed in Korea along the same neutrino beam line. By using recent geophysical measurements, we examine the earth matter effects on the oscillation probabilities at Kamioka and Korea. The average matter density along the Tokai-to-Kamioka base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…with a baseline length L. We have neglected the matter effect because it is small enough for the energy range and the baseline lengths we concern in this study [24]. In obtaining the second line of (2.4) we have also ignored the tiny energy difference between the three mass eigenstates,…”
Section: Reactor Antineutrino Fluxmentioning
confidence: 99%
“…with a baseline length L. We have neglected the matter effect because it is small enough for the energy range and the baseline lengths we concern in this study [24]. In obtaining the second line of (2.4) we have also ignored the tiny energy difference between the three mass eigenstates,…”
Section: Reactor Antineutrino Fluxmentioning
confidence: 99%
“…Ideas of extending the Tokai-to-Kamioka (T2K) experiment with additional waterČerenkov detectors placed in Korea (Tokai-to-Kamioka-and-Korea, T2KK, experiment [15][16][17][18][19][20][21][22][23][24][25][26]) or in Oki island (Tokai-to-Kamioka-and-Oki, T2KO, experiment [25,27]) have been proposed to address those questions. 1 It has been shown that the T2KK experiment with a 100 kton fiducial-volume detector in Korea in addition to the SK detector is an appealing proposal if we can use the J-PARC neutrino beam with 0.64 MW beam power and the 2.5 • -3.0 • off-axis angle at the SK [17,18,20,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been shown that the T2KK experiment with a 100 kton fiducial-volume detector in Korea in addition to the SK detector is an appealing proposal if we can use the J-PARC neutrino beam with 0.64 MW beam power and the 2.5 • -3.0 • off-axis angle at the SK [17,18,20,22,24]. The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations